Synthesis, Spectral Characterization and Application of Some Thio-azo Dyes - KURTOGLU, NURCAN; SENOL, DUYGU (Asian Journal of Chemistry, 2010)
In this study, some substituted azo compounds containing thiourea, -NH(C=S)NH- and azo -N=N- groups, (1) [N,N'-bis(4- phenylazophenylene)thiourea] (bppt), (2) [N,N'-bis(4-(4'- sodiumsulfophenylazo)phenylene)]thiourea, (bspt), (3) 4-(4'- aminophenyleneazo)-5-hydroxy-2,7-naphthalene disulfonic acid disodium salt), (ahns), (4) N,N'-bis-[4-(8-hydroxy-3,6- disulfodisodium-1-naphthylazo)phenylene]thiourea, (bhnt) were synthesized by the reaction of some aromatic amines and CS2 in EtOH. The thio-azo-dyes, (1) (bppt), (2) (bspt), (3) (ahns) and (4) (bhnt) have been characterized by the use of spectroscopic techniques such as infrared, UV-Visible, proton nuclear magnetic resonance and analytical methods. The dying properties and fastness of these dyes were investigated by applying them onto cotton and wool fibers. The applications on wool fibers were carried out by the use of direct and mordant dying methods and the applications on cotton fabric were made by direct and printing methods.